Prevalence and spectrum of germline BRCA1 and BRCA2 mutations in multiethnic cohort of breast cancer patients in Brunei Darussalam - Siti Nur Idayu Matusin; Nuramalina Mumin; Hazirah Zainal Abidin; Fatin Nurizzati Mohd Jaya; Zen Huat Lu; Mas Rina Wati Haji Abdul Hamid (PLoS ONE, 2025)
This is the first genetic study of its kind in Brunei Darussalam. BRCA1 and BRCA2 genes are the most well-known and well described predictors of hereditary breast cancer due to their clinical importance. This study aimed to identify the prevalence and mutation spectrum of the BRCA1 and BRCA2 germline mutations among 120 unselected series of Brunei breast cancer patients. We screened the entire coding region of BRCA1 and BRCA2 gene using Sanger sequencing and next-generation sequencing methods and identified three pathogenic and one likely pathogenic mutations in the BRCA2 gene. Of the 120 patients, 6 (5%) were BRCA2 carriers which confirm that BRCA2 carriers are more common in the Asian population compared to the Caucasian population. One BRCA2 mutation observed only in the Chinese ethnicity of the Brunei breast cancer population suggest a probability of the mutation being a founder effect in the Southern Chinese population. Brunei BRCA2 carriers were more likely to have a positive family history of breast and/or ovarian cancers and have more than one family members in the first-degree relatives diagnosed with breast cancer.